SIRT7 antagonizes TGF-β signaling and inhibits breast cancer metastasis - Xiaolong Tang (Nature Portfolio, 2017)
Metastatic disease is the major reason for breast cancer-related deaths; therefore, a better understanding of this process and its players is needed. Here the authors report the role of SIRT7 in inhibiting SMAD4-mediated breast cancer metastasis providing a possible therapeutic avenue.